2020
DOI: 10.1016/j.omto.2019.12.008
|View full text |Cite
|
Sign up to set email alerts
|

miR-155 Overexpression in OT-1 CD8+ T Cells Improves Anti-Tumor Activity against Low-Affinity Tumor Antigen

Abstract: Therapy by adoptive transfer of ex vivo-expanded tumor-infiltrating or genetically modified T cells may lead to impressive clinical responses. However, there is a need to improve in vivo persistence and functionality of the transferred T cells, in particular, to face the highly immunosuppressive environment of solid tumors. Here, we investigate the potential of miR-155, a microRNA known to play an important role in CD8 + T cell fitness. We show that forced expression of miR-155 in tumor antigen-specific T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…miR-155 in the tumors is derived from both cancer cells and stroma cells including immune cells. While we and others showed the anti-tumor role of immune cell miR-155 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), the role of cancer cell-derived miR-155 is more elusive or controversial (5,8). To investigate the direct impact of cancer cell-derived miR-155 on tumor progression and tumor immune infiltration, we established B-cell integration cluster (Bic, miR-155 gene) overexpressing breast cancer cell lines (EO771-Bic, 4T1-Bic, and AT-3-Bic) via lentiviral transduction; these cells express 15-60-fold higher miR-155 than control lentiviral transduced cells (EO771-GFP, 4T1-GFP, and AT-3-GFP) (Supplemental Figure 5, A-C).…”
Section: Overexpression Of Mir-155 In Breast Cancer Cells Delays Tumo...mentioning
confidence: 80%
See 1 more Smart Citation
“…miR-155 in the tumors is derived from both cancer cells and stroma cells including immune cells. While we and others showed the anti-tumor role of immune cell miR-155 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), the role of cancer cell-derived miR-155 is more elusive or controversial (5,8). To investigate the direct impact of cancer cell-derived miR-155 on tumor progression and tumor immune infiltration, we established B-cell integration cluster (Bic, miR-155 gene) overexpressing breast cancer cell lines (EO771-Bic, 4T1-Bic, and AT-3-Bic) via lentiviral transduction; these cells express 15-60-fold higher miR-155 than control lentiviral transduced cells (EO771-GFP, 4T1-GFP, and AT-3-GFP) (Supplemental Figure 5, A-C).…”
Section: Overexpression Of Mir-155 In Breast Cancer Cells Delays Tumo...mentioning
confidence: 80%
“…Nevertheless, some reports have shown that miR-155 upregulation in tumors is associated with improved overall survival of patients with several types of cancer including breast cancer, colon cancer, and melanoma (7)(8)(9). To account for this discrepancy, we and others have shown that miR-155 may play a central role in innate and adaptive immune responses (10)(11)(12)(13)(14)(15)(16). We reported that miR-155 deficiency in macrophages and myeloid-derived suppressor cells (MDSCs) promotes tumor growth by exaggerating the immunosuppressive functions of these cells (12,13).…”
Section: Introductionmentioning
confidence: 95%
“…Cytotoxic T cells are considered one of the most powerful anti-tumoral ICs, but they are often absent or dysfunctional, due to their exhaustion or to the immunosuppressive features of the TME [ 11 ]. They exert anti-tumoral activity by directly killing malignant cells through the release of granules of perforin and granzyme B. Clinically, high levels of T cells correlate with good prognosis in several cancers—such as melanoma, breast, lung, ovarian, renal, prostate, and gastric [ 99 ]—and in recent years, immunotherapy approaches have been developed to foster the anti-tumoral capacity of T cells [ 85 ].…”
Section: Micrornas (Mirs)mentioning
confidence: 99%
“…Yan and coworkers demonstrated that miR-155-induced downregulation of TIM3, a negative immune checkpoint, enhanced the cytolytic activity of anti-HCC CD8 + T cells (56). Finally, miR-155 overexpression can optimize CD8 + T cell antitumor activity and improve adoptive-transfer in low-affinity antigen tumors (57).…”
Section: Mdsc-mirs and Response To Immunotherapymentioning
confidence: 99%